Financial Technology Adoption and Digitization of Zakat Payment Behavior (UIN Sunan Kudus, 2023)
This research aims to examine the influence of digitization on zakat, with the goal of understanding the motivation to shift from conventional payment methods to digital alternatives. The alteration of Unified Theory of Acceptance and Use of Technology 2 (UTAUT) is selected by integrating perceived risk and trust. The analytic method is Partial Least Squares, with a sample size of 348 muzakki (zakat givers) observed. The results showthat theunderlying factors have a considerable influence on the development of behavioral intention, with trust playing a dual role by moderating and mediating theinteractions. These emphasize the necessity for regulators to continuously promote technological adaptability, develop sufficient infrastructure, and improve digital literacy in the community. Moreover, thesteps enhance the possibility for national zakat collection, leading to the equitable distribution of wealth